Rice Calcineurin B-Like Protein-Interacting Protein Kinase 31 (OsCIPK31) Is Involved in the Development of Panicle Apical Spikelets - Peng, Yongbin; Hou, Feixue; Bai, Que; Xu, Peizhou; Liao, Yongxiang; Zhang, Hongyu; Gu, Chaojian; Deng, Xiaoshu; Wu, Tingkai; Chen, Xiaoqiong; Ali, Asif; Wu, Xianjun (Frontiers in Plant Science, 2018)
Panicle apical abortion (PAA) causes severe yield losses in rice production, but details about its development and molecular basis remain elusive. Herein, a PAA mutant, paa1019, was identified among the progeny of an elite indica maintainer rice line Yixiang 1B (YXB) mutagenized population obtained using ethyl methyl sulfonate. The abortion rate of spikelets in paa1019 was observed up to 60%. Genetic mapping combined with Mutmap analysis revealed that LOC_Os03g20380 harbored a single bp substitution (C to T) that altered its transcript length. This gene encodes calcineurin B-like protein-interacting protein kinase 31 (OsCIPK31) localized into the cytoplasm, and is preferentially expressed in transport tissues of rice. Complementation of paa1019 by transferring the open reading frame of LOC_Os03g20380 from YXB reversed the mutant phenotype, and conversely, gene editing by knocking out of OsCIPK31 in YXB results in PAA phenotype. Our results supports that OsCIPK31 plays an important role in panicle development. We found that dysregulation is caused by disruption of OsCIPK31 function due to excessive accumulation of ROS, which ultimately lead to cell death in rice panicle. OsCIPK31 and MAPK pathway might have a synergistic effect to lead ROS accumulation in response to stresses. Meanwhile the PAA distribution is related to IAA hormone accumulation in the panicle. Our study provides an understanding towards the role of OsCIPK31 in panicle development through responding to various stresses and phytohormones.